Significance of the heritage of the Great Duchy of Lithuania in popular interpretations of the national narrative - Irena Šutinienė (Lietuvos Istorijos Studijos)
The article presents the data of empirical research (namely, a representative survey of Lithuanian adult population as well as focused interviews) of popularity and uses of symbolic representations of the period of the Great Duchy of Lithuania. About a third part of inhabitants sets a great store on the heritage of the Great Duchy of Lithuania as significant for their national identity. The myths supporting the continuity of national identity (the founding, "descent" myths) grow in popularity, while the significance of the myths serving mobilization for collective action (that of the "golden age" and others) is on the decrease.